CURRENT TRENDS IN THE DEVELOPMENT OF THE GLOBAL TOURISM SERVICES MARKET - ZHURBA, Ihor; SHCHUKA, Halyna; TSVIHUN, Yurii (Herald of Khmelnytskyi National University. Economic sciences, 2025)
The article is devoted to a comprehensive analysis of the current state and key trends shaping the development of the global tourism services market. Drawing on up-to-date statistical data provided by leading international organizations — including the UN World Tourism Organization (UNWTO), the World Travel & Tourism Council (WTTC), and the Organisation for Economic Co-operation and Development (OECD) — the study identifies the structural characteristics of the market, examines the geographical distribution of international tourist flows, and outlines the main segments of tourism supply. Special attention is given to the most significant contemporary trends that determine the trajectory of global tourism development. In particular, the authors emphasize the growing influence of digitalization and technological innovation, the expansion of sustainable and eco-friendly tourism practices, the increasing personalization of tourism products and services, and the heightened importance of safety standards for travelers in a post-pandemic environment. The article also highlights the critical role of social media platforms and digital communication ecosystems in shaping tourism demand, consumer preferences, and destination image formation. Based on the conducted analysis, the article formulates a set of practical recommendations for tourism enterprises and stakeholders. These recommendations aim to support effective adaptation to the rapidly changing global environment, enhance competitiveness, foster sustainable development, and improve strategic decision-making within the tourism sector.